Hubungan antara Kematangan Emosi dengan Perilaku Agresif pada Siswa Kelas XI SMKS Subulussalam Pasaman Barat - Diana, Elgi; Fiitria, Linda; Radyuli, Popi (YASIN, 2024)
This research aims to determine the relationship between emotional maturity and aggressive behavior in class This type of research is quantitative with correlational research methods. The research population was 354 people, with a sample of 188 people taken using a proportional random sampling technique. The instrument in this study used an emotional maturity scale whose validity had been tested with 19 items with a reliability coefficient of -0.864 and an aggressive behavior scale whose validity had been tested was 27 items. with a reliability coefficient of 0.969. Data analysis uses the Person Product Moment Correlation formula with an error tolerance of 5% using statistical programs on the computer SPSS 23 and Microsoft Excel. Based on the hypothesis results, the rcount value is -0.864, while the rtable value is 0.142, So there is a negative relationship between emotional maturity and students' aggressive behavior.